Characterization of m6A Methylation Modification Patterns in Colorectal Cancer Determines Prognosis and Tumor Microenvironment Infiltration - Qingfang Yue; Yuan Zhang; Fei Wang; Fei Cao; Jun Bai; Xianglong Duan (Journal of Immunology Research)
Cumulative studies have suggested that dysregulation of m6A regulators and immunity is highly linked to the prognosis of patients with cancer. However, the potential contribution of m6A modification patterns to the tumor microenvironment (TME) and the therapeutic efficacy of immunotherapy for colorectal cancer (CRC) remain elusive. A comprehensive analysis of the m6A modification profiles of 458 patients with CRC was performed by clustering 21 genes encoding m6A methylation regulators and linking the m6A modification pattern with TME characteristics. Using principal component analysis (PCA), a risk model was constructed to quantify individual m6A modification patterns in patients with CRC. The results indicated that the expression profiles and genetic mutations of 21 genes encoding m6A methylation regulators in CRC were characterized by a high degree of heterogeneity. Three m6A clusters had significant differences in prognosis, m6A modification patterns, and TME characteristics. Furthermore, a risk model, termed m6Ascore, was developed by PCA to quality m6A methylation patterns at an individual level. The m6Ascore could stratify patients into high- and low-m6Ascore groups. Further analyses demonstrated that the m6Ascore had a good predictive performance for overall survival and clinical efficacy of immunotherapy in patients with CRC. Finally, the predictive value of the model was validated by external cohorts. In conclusion, the comprehensive characterization of m6A methylation modification patterns might contribute to our understanding of the TME in CRC and the development of personalized antitumor immunotherapy in the future.